Extracellular vesicles in dry eye disease and Sjögren’s syndrome: A systematic review on their diagnostic and therapeutic role - Chopra, Prakshi; Fatima, Asra; Mohapatra, Sonali; Murugaiyan, Kavipriya; Vemuganti, Geeta K.; Rengan, Aravind Kumar; Watson, Stephanie L.; Singh, Vivek; Basu, Sayan; Singh, Swati (Survey of ophthalmology, 2025)
Extracellular vesicles (EVs), defined as membrane-bound vesicles released from all cells, are being explored for their diagnostic and therapeutic role in dry eye disease (DED). We systematically shortlisted 32 articles on the role of EVs in diagnosing and treating DED. We cover the progress in the last 2 decades on the classification and isolation of EVs and their role in DED. The diagnostic predictability of exosomes was evaluated in Sjögren syndrome (SS) patients' tears, plasma, and saliva, where upregulation of inflammatory proteins was reported uniformly across studies. Also, we evaluate the therapeutic effects of MSC-derived EVs in in vitro and in vivo studies of SS and DED mouse models. A significant response occurs at a functional level with improved tear production and saliva flow rate and at a cellular level with reduced lymphocyte infiltration, improved corneal structural integrity, decreased epithelial cell apoptosis, and dampening of the inflammatory cytokine response. The proposed mechanisms of EV action include PD-L1, PRDM, NLRP-3, and Nf-kb pathways, and an increase in M2 macrophage phenotype. Current use of exosomes in DED is limited due to their cumbersome isolation techniqus. Further research on human subjects is needed, in addition to optimizing exosome isolation and delivery methods.